2012
DOI: 10.1016/j.bbr.2011.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in detection of spatial novelty

Abstract: Age-related changes in novelty detection for object-place associations was assessed in 6-mo and 25-mo-old Fisher 344/Brown Norway (F344/BN) rats. Old rats showed significant deficits compared to young rats in detecting spatial displacement of objects. The data suggest that object-place novelty detection is impaired in aged F344/BN rats using a rapidly acquired, exploratory-based task. The results may have important implications for the selection of efficient memory paradigms for future aging studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…This may be related to the fact that with the movement of the already familiar object a less subtle spatial and/or environmental change took place. Studies reporting age‐related short‐term deficits in the object place task, however, also have been reported though in a different rat strain, testing procedure and mainly in a much older cohort (Shukitt‐Hale et al, ; Maasberg et al, ). It implies that the sensitivity of detected age‐related deficits may rely on the specific rat strain, test and aging stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to the fact that with the movement of the already familiar object a less subtle spatial and/or environmental change took place. Studies reporting age‐related short‐term deficits in the object place task, however, also have been reported though in a different rat strain, testing procedure and mainly in a much older cohort (Shukitt‐Hale et al, ; Maasberg et al, ). It implies that the sensitivity of detected age‐related deficits may rely on the specific rat strain, test and aging stage.…”
Section: Discussionmentioning
confidence: 99%
“…Male Wistar rats (7‐8 weeks and 7‐8 months old) were housed in groups of four and maintained on a 12‐h light/12‐h dark cycle. Seven‐to eight‐month‐old rats were considered “older” to distinguish them from work conducted with “aged” rats of more than 20 months (Shukitt‐Hale et al, ; Maasberg et al, ). The animals were assessed in parallel as two separate cohorts.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, age-related structural and physiological changes in the neural system involved in spatial recognition memory, such as hippocampal formation ( Akkerman et al 2012 ; Maasberg et al 2012 ), can be a main target of EGb through modulating molecular mechanisms related to memory loss. We have demonstrated that 1.0 g/kg EGb improved short-term spatial memory and preventive effects in the prefrontal cortex in middle-aged rats ( Ribeiro et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study with animals aimed at examining age-related changes in the detection of spatial novelty (e.g., M et al 3 ), namely, verifying if old rats showed signi cant de cits compared to young rats in detecting spatial displacement of objects, showed that aged rats do not detect changes in object-place associations when exploring an environment. In this regard, some studies in elderly and young population investigating the neural correlates of aging-related changes during encoding and retrieval of spatial contextual memory (e.g., K et al 4 ) and aspects of episodic memory (e.g., P et al…”
Section: Introductionmentioning
confidence: 99%